THE JUSTICE IN CREDIT AGREEMENTS WITH CLAUSULA STANDARD - Lathifah Hanim (UNISSULA, 2020)
Standard agreements have long been used in various contracts, the use of standard agreements is closely related to advances in the economy that require efficiency in spending costs, time and energy. A standard agreement is an agreement whose terms are standardized or determined by one party only, while the other party can only agree to it. The research objective is to determine and analyze the fairness of the credit agreement in the presence of standard clausulas. The research method uses juridical empirical. The results of the research are Contract justice can be seen in an agreement when both parties reach an agreement to bind themselves together without any pressure from other parties, in this case the contract is carried out voluntarily. Negotiations carried out in an agreement can also avoid one-sided contracts, and this is one of the first steps in creating a fair contract.